Effects of Low Frequency-Low Voltage Alternating Electric Current on Apoptosis Progression in Bioelectrical Reactor Biofilm - Hoseinzadeh, Edris; Wei, Chiang; Farzadkia, Mahdi; Rezaee, Abbas (Frontiers in Bioengineering and Biotechnology, 2020)
Bioelectrochemical systems have undergone several modifications to promote the enzymes or pathways used to reduce the energy required for microbial metabolism. Changes in dominant bacteria, population, and growth rates occur when an electric current is applied intermittently. Applying electricity to bioelectrical reactor (BER) biofilms can either stimulate cells or lead to cell death; therefore, determining the applied voltage range that leads to viable and stimulated bacteria is crucial. We investigated the progression of apoptosis induced by a low frequency-low voltage alternating electric current (AC) in a BER biofilm and found that biofilms on carbon cloth (CC) and stainless steel (SS) 304 electrodes had pHzpc values of 8.67. The pHzpc of the biofilms increased by two compared to that of the inoculant bacteria mass. Furthermore, the Henderson–Hasselbalch equation reveals that the compositions of cell walls of the biofilms that formed on the CC and SS304 electrodes are very similar. In contrast, the CC and SS304 biofilms differ from the inoculant biomass without the influence of an AC field; this indicates that there are differences in the compositions of the cell walls in the present bacteria. Fourier transform infrared spectroscopy was used to compare spectra of the biofilms with that of the inoculation mass, and there were differences in shape and absorbance intensity, indicating variability in the composition, and quantity of each individual biofilm component. In addition, the dehydrogenase activity (DHA) content varied under different applied voltages; the highest DHA was obtained at 8 Vpp. A flow cytometry analysis showed a relatively low number of apoptotic cells (10.93 ± 5.19%) for the AC amplitudes studied. Thus, a low voltage-low frequency AC likely induces significant changes in bacterial metabolic activity but causes no significant change in their viability.